2008
DOI: 10.5713/ajas.2008.70565
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Varying Ruminally Degradable to Undegradable Protein Ratio on Nutrient Intake, Milk Yield, Nitrogen Balance, Conception Rate and Days Open in Early Lactating Nili-Ravi Buffaloes (Bubalus bubalis)

Abstract: Twenty four early lactating Nili-Ravi buffaloes, eight in each group, were used in a Randomized Complete Block Design to evaluate the influence of varying ruminally degradable protein (RDP) to ruminally undegradable protein (RUP) ratio on feed intake, digestibility, N balance, milk yield and its composition, conception rate and days open. Three experimental diets were formulated to contain RDP:RUP of 50:50, 66:34 and 82:18 and were denoted as HRUP, MRUP and LRUP, respectively. Dry matter (DM) intake was higher… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(17 citation statements)
references
References 46 publications
1
15
0
Order By: Relevance
“…Moreover, independently from blood urea levels, a lower ammonia diffusion in the buffalo uterus has been hypothesized compared to cattle, which would contribute to mitigating the detrimental effects of ammonia on embryonic development [46]. However, a negative correlation between blood urea and buffaloes' reproductive efficiency has been highlighted in other studies [23,75,76]. The lack of the effects observed herein could be also attributed to the interference of reproductive seasonality, since the increase in daylight hours tends to penalize fertility in female buffaloes, suppressing or masking any potential relationship with dietary treatments [23].…”
Section: Metabolic Profile and Reproduction Responsesmentioning
confidence: 99%
“…Moreover, independently from blood urea levels, a lower ammonia diffusion in the buffalo uterus has been hypothesized compared to cattle, which would contribute to mitigating the detrimental effects of ammonia on embryonic development [46]. However, a negative correlation between blood urea and buffaloes' reproductive efficiency has been highlighted in other studies [23,75,76]. The lack of the effects observed herein could be also attributed to the interference of reproductive seasonality, since the increase in daylight hours tends to penalize fertility in female buffaloes, suppressing or masking any potential relationship with dietary treatments [23].…”
Section: Metabolic Profile and Reproduction Responsesmentioning
confidence: 99%
“…Jonker et al (1998) reported positive correlation between MUN and urinary N excretion. The BUN and MUN were lower in buffaloes fed 50% RUP compared to those fed 34 and 18% RUP (Nisa et al, 2008). The high correlation existed between BUN and MUN concentrations (Broderick and Clayton, 1997) The degree of correlation between BUN and MUN was 0.84 (Roseler et al, 1993), 0.88 (Oltner andWiktorsson, 1983) and0.98 (Olmer et al, 1985).…”
Section: Resultsmentioning
confidence: 99%
“…This nutrient uncoupling is responsible for the reduced animal productivity and excessive nutrients losses. The protein is included in limiting nutrients in ruminants (Nisa et al, 2008). More than 50% of consumed protein in ruminants is degraded to peptides, AA and ammonia by ruminal microbial action.…”
Section: Introductionmentioning
confidence: 99%
“…A high ME in cassava meal is due to its high starch content (Garcia & Dale, 1999). In addition to high energy content, coconut meal is also a good source of protein as 70% of its protein is by-pass protein (Deville et al, 1980) which will contribute to a high milk yield (Nisa et al, 2008). Compared to these 2 supplements, palm oil solid waste only contains 12 MJ/kg ME, but it contains much higher protein (12% vs 2.5%) than that cassava meal.…”
Section: Nutritive Value Of Forage and The Supplementmentioning
confidence: 99%